Early detection of cardiac involvement in systemic sclerosis assessed by tissue-Doppler echocardiography: relationship with neurohormonal activation and endothelial dysfunction. - Dimitroulas, T; Giannakoulas, G; Papadopoulou, K; Karvounis, H; Dimitroula, H; Koliakos, G; Karamitsos, T; Parcharidou, D; Settas, L (2010)
OBJECTIVE: Cardiopulmonary complications are common in patients with systemic sclerosis (SSc). We assessed cardiac involvement in patients with SSc using echocardiography and investigated the association of N-terminal pro-brain natriuretic peptide (NT-proBNP) and asymmetric dimethylarginine (ADMA) with echocardiographic measures of myocardial function in sera of patients with SSc who had no symptoms of heart failure. METHODS: We prospectively studied 52 patients with SSc (mean age 55.7 +/- 10.1 yrs, 51 women), with conventional and tissue-Doppler echocardiography. Plasma NT-proBNP and ADMA levels were measured in all patients. Data were compared with those obtained from 25 healthy controls comparable for age and sex. RESULTS: Patients with SSc had impaired left ventricular (LV) and right ventricular diastolic function expressed by inverted ratio of peak early to peak late transmitral (Mit E/A) and transtricuspid velocity and increased left atrial diameter compared with controls. Peak systolic mitral lateral annular motion velocity and peak early diastolic mitral lateral annular motion velocity (LV Em) were lower, while LV E/Em ratio was higher, in patients with SSc compared to controls. ADMA was significantly related with LV Em and E/Em ratio. NT-proBNP was associated with Mit E, Mit E/A ratio and mitral deceleration time. Significant correlation was also observed between NT-proBNP and ADMA levels. CONCLUSION: Depressed cardiac function is common, even in asymptomatic patients with SSc. NT-proBNP and ADMA are significantly correlated with echocardiographic abnormalities, providing a potent link for cardiac function, neuroendocrine derangement, and endothelial dysfunction in patients with SSc who have cardiac disease.